PENGARUH LITERASI KEUANGAN, BRAND IMAGE DAN RELIGIUSITAS TERHADAP MINAT MENABUNG MASYARAKAT JABODETABEK PADA BANK SYARIAH - Ihwan Aindi Syaifullah, (2021)
This review expects to dissect the impact of financial literacy, brand image, and religiousity on the overall population's premium, particularly Jabodetabek in Islamic banks. Scientists utilized essential information acquired from appropriating surveys to the overall population utilizing Google Form with an absolute example of 105 respondents. Deciding the quantity of tests utilizing the Lemeshow recipe. The exploration technique utilized in this review is quantitative with information assortment strategies utilizing purposive testing strategy. The information investigation methods in this review were legitimacy tests, dependability tests, traditional presumption tests, various straight relapse tests and theory testing with the assistance of the Statistical Package for the Social Sciences (SPSS) rendition 25 programming. The aftereffects of the review showed that financial literacy and brand image had no effect for revenue in the overall population to utilize Islamic banks. Different outcomes additionally show that religiousity significantly affect overall population premium utilizing Islamic banks.